Activity-Dependent Synapse Modulation and the Pathogenesis of Alzheimer Disease - Nelson, Phillip G. (Current Alzheimer Research, 2005)
During normal development of the nervous system, a major reduction occurs in the initially excessive number of neurons and synapses. This
Keywords: presenilins